Increased leukotriene and prostaglandin release, and overactivity in the chronically ischemic bladder - TARCAN, TUFAN (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Purpose: Chronic ischemia has been shown to alter bladder contractility. We studied the roles of cyclooxygenase (COX) and lipoxygenase products in ischemia induced bladder overactivity in the rabbit. Materials and Methods: A total of 28 male New Zealand White rabbits were divided into 2 groups. In group 1 atherosclerotic occlusion of the iliac arteries was induced by balloon endothelial injury, followed by a short period of a high cholesterol diet. Group 2 received a regular diet alone. After 12 weeks blood flow measurements and cystometry were performed. Bladder tissues were processed for enzyme immunoassay of leukotrienes and prostaglandins (PGS), Western blotting of COX and lipoxygenase, isometric tension measurement and histology. Results: Atherosclerotic occlusion of the iliac arteries significantly decreased bladder blood flow. Moderate ischemia caused bladder overactivity, while severe ischemia inhibited bladder contractions. Ischemia increased leukotriene B4, E4 and C4 release by 141%, 132% and 254%, and increased PG F2alpha and thromboxane A2 release by 95% and 93%, respectively, although it did not alter PG E2 release. Western blotting showed increased 5-lipoxygenase, COX-1 and COX-2 protein levels in ischemic bladder tissues. Moderate ischemia increased bladder smooth muscle contraction in response to carbachol and electrical field stimulation. Tissue treatment with the COX inhibitor indomethacin significantly increased control tissue contraction but had no effect on ischemic tissues. Treatment with the 5-lipoxygenase inhibitor REV5901 abolished this effect of indomethacin in control tissues. Treatment with REV5901 significantly decreased the contraction of ischemic tissues but had no significant effect on control tissues. The effect of indomethacin plus REV5901 was similar to the effect of REV5901 alone. Histology showed urothelial thickening and mild fibrosis in the moderately ischemic bladder. Conclusions: Chronic ischemia increased bladder 5-lipoxygenase, and COX-1 and COX-2 protein expression, and altered leukotriene and PG production. Treatment with COX and lipoxygenase inhibitors produced completely different effects in the ischemic bladder compared with the control bladder. Functional changes in the ischemic bladder were concurrent with structural changes in the urothelium. PGs modulate smooth muscle contractility in the healthy bladder. However, under ischemic conditions leukotrienes dominate bladder tone and appear to have a leading role in increased smooth muscle contraction and bladder overactivity.
Keywords: bladder; leukotrienes; prostaglandins; rabbits; ischemia; IN-VITRO CHANGES; SMOOTH-MUSCLE; SENSITIZATION; OVALBUMIN; OCCUR; VIVO